Investigation of the miRNA-mRNA Regulatory Circuits and Immune Signatures Associated with Bronchopulmonary Dysplasia - Li S; Liang S; Xie S; Chen H; Huang H; He Q; Zhang H; Wang X (Dove Medical Press, 2024)
Sen Li,1 Shuling Liang,2 Shunyu Xie,1 Haixia Chen,1 Haoying Huang,1 Qixin He,3 Huayan Zhang,4,5 Xiaohui Wang1 1Guangzhou Women and Children's Medical Center, State Key Laboratory of Respiratory Disease and Guangzhou Medical University, Guangzhou, Guangdong Province, People's Republic of China; 2Guangdong Provincial Research Center for Child Health, Guangzhou Women and Children's Medical Center, Guangzhou Medical University, Guangzhou, Guangdong Province, People's Republic of China; 3Sun Yat-sen University Cancer Center, Guangzhou, Guangdong Province, People's Republic of China; 4Division of Neonatology and Center for Newborn Care, Guangzhou Women and Children's Medical Center, Guangzhou, Guangdong Province, People's Republic of China; 5Division of Neonatology, Department of Pediatrics, Children's Hospital of Philadelphia and University of Pennsylvania Perelman School of Medicine, Philadelphia, PA, USACorrespondence: Xiaohui Wang; Huayan Zhang, Email xiaohuiwang2021621818@gzhmu.edu.cn; zhangh@chop.eduBackground: Bronchopulmonary dysplasia (BPD) has become a major cause of morbidity and mortality in preterm infants worldwide, yet its pathogenesis and underlying mechanisms remain poorly understood. The present study sought to explore microRNA-mRNA regulatory networks and immune cells involvement in BPD through a combination of bioinformatic analysis and experimental validation.Methods: MicroRNA and mRNA microarray datasets were obtained from the Gene Expression Omnibus (GEO) database. Differentially expressed microRNAs (DEMs) were identified in BPD patients compared to control subjects, and their target genes were predicted using miRWalk, miRNet, miRDB, and TargetScan databases. Subsequently, protein-protein interaction (PPI) and functional enrichment analyses were conducted on the target genes. 30 hub genes were screened using the Cytohubba plugin of the Cytoscape software. Additionally, mRNA microarray data was utilized to validate the expression of hub genes and to perform immune infiltration analysis. Finally, real-time PCR (RT-PCR), immunohistochemistry (IHC), and flow cytometry were conducted using a mouse model of BPD to confirm the bioinformatics findings.Results: Two DEMs (miR-15b-5p and miR-20a-5p) targeting genes primarily involved in the regulation of cell cycle phase transition, ubiquitin ligase complex, protein serine/threonine kinase activity, and MAPK signaling pathway were identified. APP and four autophagy-related genes (DLC1, PARP1, NLRC4, and NRG1) were differentially expressed in the mRNA microarray dataset. Analysis of immune infiltration revealed significant differences in levels of neutrophils and naive B cells between BPD patients and control subjects. RT-PCR and IHC confirmed reduced expression of APP in a mouse model of BPD. Although the proportion of total neutrophils did not change appreciably, the activation of neutrophils, marked by loss of CD62L, was significantly increased in BPD mice.Conclusion: Downregulation of APP mediated by miR-15b-5p and miR-20a-5p may be associated with the development of BPD. Additionally, increased CD62L− neutrophil subset might be important for the immune-mediated injury in BPD.Keywords: bronchopulmonary dysplasia, CD62L− neutrophil, immune infiltration analysis, miRNA-mRNA regulatory circuits